2014
DOI: 10.1039/c3nr06610j
|View full text |Cite
|
Sign up to set email alerts
|

Local structural investigation of Eu3+-doped BaTiO3nanocrystals

Abstract: A structural investigation of sub-15 nm xEu:BaTiO3 nanocrystals (x = 0-5 mol%) was conducted to determine the distribution of the Eu(3+) ion in the BaTiO3 lattice. Pair distribution function analysis of X-ray total scattering data (PDF), steady-state photoluminescence, and X-ray absorption spectroscopy (XANES/EXAFS) were employed to interrogate the crystal structure of the nanocrystals and the local atomic environment of the Eu(3+) ion. The solubility limit of the Eu(3+) ion in the nanocrystalline BaTiO3 host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…Note that the peak intensity at both 779.4 eV and 794.6 eV increases with the increase in Nd concentration, suggesting that Ba vacancy would boost with the introduction of Nd ions. In order to reach charge balance, the substitution of Nd 3+ for Ba 2+ would either convert Ti 4+ to Ti 3+ or generate Ti vacancies 163435. As reported in the literature3637, the existence of Ti 3+ ions would lead to the broad of the Ti 2p peak and a lower binding energy shoulder belonging to 2p 3/2 peak at ~456 eV.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Note that the peak intensity at both 779.4 eV and 794.6 eV increases with the increase in Nd concentration, suggesting that Ba vacancy would boost with the introduction of Nd ions. In order to reach charge balance, the substitution of Nd 3+ for Ba 2+ would either convert Ti 4+ to Ti 3+ or generate Ti vacancies 163435. As reported in the literature3637, the existence of Ti 3+ ions would lead to the broad of the Ti 2p peak and a lower binding energy shoulder belonging to 2p 3/2 peak at ~456 eV.…”
Section: Resultsmentioning
confidence: 89%
“…Theoretical calculations in terms of tolerance factor have indicated that the occupation of the exotic ions depends on their radius1415. Since the radius of RE ions is usually between Ba 2+ (1.35 Å) and Ti 4+ (0.68 Å), larger RE 3+ ions such as La 3+ (1.15 Å) and Nd 3+ (1.08 Å) prefer to substitute for the Ba 2+ -site (A-site), and the smaller ones such as Yb 3+ (0.87 Å) may locate exclusively at the Ti 4+ -site (B-site), while the intermediate ones such as Y 3+ (0.93 Å) and Er 3+ (0.96 Å) may occupy both the A- and B- sites1617. Accompanying with the specific doping, chemical inhomogeneity is often introduced.…”
mentioning
confidence: 99%
“…The minute incorporation of RE ions in barium titanate can extend its functionality towards 45 phosphor based applications including field emission displays, light emitting devices, remote temperature sensors, and security purposes. The structural information of this material can also be easily 50 obtained by monitoring the luminescence through doping of small quantity of RE ions [14]. The structural information of this material can also be easily 50 obtained by monitoring the luminescence through doping of small quantity of RE ions [14].…”
Section: Introductionmentioning
confidence: 99%
“…The second band, centered at 375 nm, could be related to the charge transfer from cationic or anionic defects to Eu 3? [7,8], while the band at 394 nm corresponds to 7 F 0 ? 5 L 6 transitions of Eu 3? .…”
Section: Photoluminescence Characterization Of Batio 3 : Eu 3? Nanopamentioning
confidence: 99%
“…, Er 3? and Eu 3? [5][6][7]. Doping BaTiO 3 and other hosts with lanthanides is promising, not only to produce luminescent materials for applications in field emission displays, solid-state lamps and lasers, but also to serve as precursors for grained ceramics, which can be employed in ferroelectric capacitors and thermistors [7][8][9].…”
Section: Introductionmentioning
confidence: 99%